PERAN KEPOLISIAN DALAM PENANGANAN KASUS NARKOTIKA DI INDONESIA - Tefi, Natanael Andreas (Journal of Law ( Jurnal Ilmu Hukum ), 2025)
ABSTRACT. The role of the police is very important in handling drug cases because they have the authority and responsibility to enforce the law in accordance with applicable regulations. One of the law enforcement officials who plays a crucial role in addressing drug abuse cases is the 'investigator', in this case, the police officers assigned to the narcotics division. This study discusses the role of the police in handling drug cases in Indonesia according to the relevant laws and regulations, as well as the challenges faced by the police in the investigation and handling of drug cases. This research is empirical law, examining based on the concepts of principles and laws related to this scholarly writing, usually referred to as library study, which involves studying regulations, books, documents, and others related to this writing. The role of the police in handling narcotics cases in Indonesia is very important and is clearly regulated in various laws and regulations, including Law Number 35 of 2009 on Narcotics and Law Number 2 of 2002 on the Police. However, the obstacles are very complex from various aspects. Starting from limited human resources and technology, low coordination between agencies, the complexity of international narcotics networks, to internal corruption within the police force, all these factors complicate efforts to eradicate narcotics. Keywords: The Role of the Police, Narcotics, Investigation.